Energy Profile Evaluation of a Cyber-Physical System - Moraes, Elisabete Nakoneczny; Becker, Leandro Buss (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
In Cyber-Physical Systems (CPS) the operation of electromechanical devices is tightly integrated with the embedded computer system. The diversity of components imply in different profiles of energy consumption. Thereby, it becomes useful to use techniques that can manage the energy consumption. In a previous work, this aspect was modeled using a technique that allows estimating the energy consumption of a battery-powered CPS. In this paper we present a practical implementation of such work, where the peripherals of a mobile robotic system are characterized to compose the energy profile of the system. Conducted experiments measured the electrical currents during a planned navigation of the robot. The results confirm the assumptions assumed by the modeling technique, which proposes a relationship between the embedded computer system and the electromechanical devices, i.e., there is a direct relation between the device's activation and the nature of the software task under execution.